ANALISIS DAN PENERAPAN METODE LINE OF BALANCE PADA PROYEK REPETITIF - Regentino Sinaga; Pinondang Simanjuntak; Setiyadi (UKI Press, 2021)
Line of Balance is an effective scheduling method used on projects with repetitive work. The Line of Balance method is able to present productivity levels and duration information in the form of a line graph format that is easier to understand so that it can identify errors that occur in the progress of activities. The purpose of this study was to reschedule the construction project of the Ministry of Finance building in Bandar Lampung using the LoB method to determine the level of time effectiveness and cost efficiency, where initially the project was planned using the Bar Chart method of the s curve. Line of Balance (LoB) is one of the linear scheduling methods that allows balance of application so that each activity can continue. In this final project, the procedure carried out by this research is calculated by using the Line of Balance (LoB) method to simplify the activities so that it is easier to analyze conflicts that occur after drawing them into line diagrams. The calculation results obtained in this planning using the Line of Balance method after merging activities, conflict analysis and drawing diagrams obtained the final duration of work 270 days. while the scheduling using the barchat s-curve method takes 273 days, which means the difference in scheduling using the Line of Balance method to complete the construction project of the Ministry of Finance building in Bandar Lampung is three days faster (0.98%).